Investigating the diversity of arbuscular mycorrhizal fungi from Gymnema sylvestre and Curcuma longa in Vietnam - Kim Chi, Hoang; Nhu Hang, Tran Thi; Hong Ha, Tran Thi; Huu Cuong, Le; Ho Quang, Tran; Anh Van, Bui; Hoang Yen, Le Thi; Mai Huong, Le (Vietnam Journal of Biotechnology, 2020)
Arbuscular mycorrhizal (AM) fungi are soil eukaryotes that belong to phylum Glomeromycota and have symbiosis with the vast majority of higher plants’ roots. AM fungi are believed to be coevolved with terrestrial plants, the abundance and diversity of AM fungal communities as a result are host plant dependent. A survey of AM fungi from the rhizospheres of medicinal plants in Northern Vietnam including gurma Gymnema sylvestre and turmeric Curcuma longa was carried out. From the extracted total DNAs of the medicinal plants’ rhizosphere soil samples, 35 mycorrhizal fungal species were identified by analyzing small subunit rRNA gene sequences. Result revealed that genus Glomus is the most abundant in the AM communities of G. sylvestre and C. longa, followed by Gigaspora and Acaulospora. Besides, AM species belonging to genera Scutellospora, Diversispora and Rhizophagus were observed in almost all rhizosphere soil samples. The spore counting by wet sieving and decanting method uncovered a variation in AM spore density of gurma and turmeric rhizosphere. In general, AM species were found more abundantly and more diverse in collected rhizome soil samples of C. longa (27 species belonging to 10 genera) than of G. sylvestre (17 species found belonging to 7 genera). The observed difference in AM communities of G. sylvestre and C. longa supports evidence for the dependence of AM fungal species on host plants, and indicates that AM fungi may have relation to the host plants’ secondary metabolite production.